From war to integration: generalizing the dynamic of power transitions - Brian Efird; Jacek Kugler; Gaspare M. Genna (Claremont McKenna College, Department of Economics, 2003)
Generalizing the dynamics implied by power transition theory, we characterize the structural conditions that lead nations to initiate conflict or choose to integrate. The relationship between changes in relative power, hierarchical structures, and joint satisfaction are used to identify the structural conditions for conflict and cooperation. Empirical tests for the last two centuries confirm the strength and robustness of this characterization. In addition, long term assessments of Pax Britannica, the Cold War, and China's potential challenge to the United States in this century are used to illustrate the precision of these findings. The fundamental implication is that structural conditions provide the pre-conditions for conflict and cooperation, but decision makers have leeway in advancing policies that eventually lead to either war or peace.
Keywords: 330